Management of people with diabetes during Ramadan. - (:unkn) unknown (My University, 2002)
In the UK, Islam is the second largest religion after Christianity and there are about 2.5 million Muslims living in the UK. Fasting is obligatory for all healthy adult Muslims during the holy month of Ramadan. During Ramadan, no food, drink, or medication is allowed between dawn and sunset. As a result of different research results there is no agreement on whether it is safe for Muslim diabetics to fast. Through dialogue between health professionals and patients, it is usually possible to facilitate at least some safe fasting for those who wish to observe this annual ritual. In this article some key pointers will be given for health professionals to consider with the aim of improving the quality of care of Muslim patients with diabetes during Ramadan.